1987
DOI: 10.1148/radiographics.7.4.3448653
|View full text |Cite
|
Sign up to set email alerts
|

The continuum of pulmonary developmental anomalies.

Abstract: The classic features of six common pulmonary developmental anomalies have been presented. In addition, several overlap cases, each demonstrating features of more than one anomaly, have been illustrated. Such cases serve to emphasize that pulmonary developmental anomalies exist as a continuum, often frustrating our attempts at discrete classification. Future advances in pulmonary embryology may further elucidate the pathogenesis of these entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 0 publications
0
20
1
5
Order By: Relevance
“…The molecular basis is thought to be excessive platelet derived growth factor BB which leads to increased cell proliferation and decreased cell apoptosis in utero. The condition is part of the continuum of pulmonary developmental anomalies described by Panicek et al (4). Traditionally, the condition is classified into three types according to Stocker et al (5).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis is thought to be excessive platelet derived growth factor BB which leads to increased cell proliferation and decreased cell apoptosis in utero. The condition is part of the continuum of pulmonary developmental anomalies described by Panicek et al (4). Traditionally, the condition is classified into three types according to Stocker et al (5).…”
Section: Discussionmentioning
confidence: 99%
“…CLM can show predominantly parenchymal or predominantly vascular anomalies, or a combination of both (Table 1).They occur as a continuum of abnormalities [3], with the presence of lung parenchymal abnormality and normal vasculature on one hand (in congenital pulmonary airway malformation-CPAM, and congenital lobar hyperinflation-CLH) and abnormal vasculature in the absence of parenchymal abnormality on the other hand (pulmonary arterio-venous malformations-AVMs). Many cases have features overlapping between two or more conditions ('hybrid' lesions)-for instance CPAM-like changes in an area of 'sequestered' lung [4,5].…”
Section: Spectrum Of Congenital Lung Malformationsmentioning
confidence: 99%
“…For a long time, the most widely accepted theory of etiopathogenesis was that of defective budding, separation, and differentiation of primitive foregut structures [3,6,7]. Langston [8] proposed that many lesions could be explained to occur as a result of airway obstruction leading to secondary pulmonary dysplastic changes.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Histological studies of lung masses obtained from postnatal thoracic surgery have shown that there may be more than one diagnosis attributed to the same lesion 5 . This has led to the assumption that the above-mentioned four diagnoses may in fact be the same interrelated abnormality of a hybrid lung lesion 6,7 . The presumed mechanism leading to increased NT is increased superior mediastinal compression, which is commonly associated with fetal structural defects such as CDH, Fryns' syndrome and CCAM, or narrow chest in skeletal dysplasias such as osteogenesis Type II, thanatophoric dysplasia or asphyxiating thoracic dystrophy.…”
Section: Congenital Lobar Emphysema and Increased Nuchal Translucencymentioning
confidence: 99%